Assessment of appropriate body mass index cut-off points for long-term mortality among ST-elevation myocardial infarction survivors in Asian population using machine learning algorithm - Yoshioka, Naoki; Takagi, Kensuke; Tanaka, Akihito; Morita, Yasuhiro; Yoshida, Ruka; Nagai, Hiroaki; Kanzaki, Yasunori; Watanabe, Naoki; Yamauchi, Ryota; Komeyama, Shotaro; Sugiyama, Hiroki; Shimojo, Kazuki; et al. (Heart and vessels, 2022)
Low body mass index (BMI) is a predictor of adverse events in patients with ST-elevated myocardial infarction (STEMI) in Western countries. Because the average BMI of Asians is significantly lower than that of the Western population, the appropriate cut-off BMI value and its role in long-term mortality are unclear in Asian patients. Between January 2006 and December 2017, 1215 patients who underwent percutaneous coronary intervention (PCI) for acute STEMI and were alive at discharge (mean age, 67.7 years; male, 75.4%) were evaluated. The cut-off BMI value, which could predict all-cause mortality within 10 years, was detected using a survival classification and regression tree (CART) model. The causes of death according to the BMI value were evaluated in each group. Based on the CART model, the patients were divided into three groups (BMI < 18 kg/m 2 : 54 patients, 18 kg/m 2 ≤ BMI ≤ 20 kg/m 2 : 109 patients, and BMI > 20 kg/m 2 : 1052 patients). The BMI decreased with age; with an increased BMI, patients with dyslipidemia, diabetes mellitus, and smoking habit increased. During the study period (median, 4.9 years), 194 patients (26.8%) died (cardiac death, 59 patients; non-cardiac death, 135 patients). All-cause mortality was more frequent as the BMI decreased (BMI < 18 kg/m 2 ; 72.8%, 18 kg/m 2 ≤ BMI ≤ 20 kg/m 2 ; 40.5%, and BMI > 20 kg/m 2 ; 22.8%; log-rank p < 0.001). Non-cardiac deaths were more frequent than cardiac deaths in all groups, and the dominance of non-cardiac death was highest in the lowest BMI group. Cut-off BMI values of 18 kg/m 2 and 20 kg/m 2 can predict long-term mortality after PCI in Asian STEMI survivors, whose cut-off value is lower than that in the Western populations. The main causes of death in this cohort differed according to the BMI values.